Restructuring of the international clothing and textile trade network: The role of Italy and Portugal - Marlies Hanna Schütz; Nicole Palan (Journal of Economic Structures, 2016)
Since the 1990s, the clothing and textile (C&T)-industry has been tremendously affected by changes in technology, trade costs, and the institutional environment. This paper studies the restructuring of C&T-trade from the perspective of Europe's two most prominent C&T-goods producing countries-Italy and Portugal. We explore these two countries' situation in a global context and concentrate our analysis to two distinct economic variables, C&T-value added and C&T-labor. Moreover, we contribute to the existing literature by distinguishing between domestically and internationally traded C&T-goods as well as between trade in intermediate and final demand C&T-goods, which enables us to give a more full-fledged picture on restructuring of C&T-trade. We show that international C&T-production became more concentrated between 1995 and 2009. In a further step, we investigate changes with regard to import penetration of C&T-trade, international outsourcing, the distance to final demand for C&T-goods, and another range of country-specific trade patterns. Our main findings reveal that Italy was more oriented toward C&T-production activities which generate high value added, whereas Portugal was less productive and relatively more specialized into the production of labor-intensive C&T-goods. Thus, Portugal was more prone to the rising international pressure from low-wage countries, whereas in Italy restructuring of C&Ttrade had comparatively less severe effects.
Keywords: C67; F14; O12; 330; Restructuring; Clothing and textile industry; International trade network; Trade of intermediate and final demand C&T-goods; Directly embodied C&T-value added and -labor; Italy and Portugal